2030 Global Education Agenda and Challenges Before India. (June 2019) - Singh, Kishore
Education of which both the individual and society are beneficiaries has a key role in the implementation of the 2030 Sustainable Development Agenda. Education is the foundation of development and all sustainable development goals (SDGs) have educational dimensions. This imparts added significance to the pursuit of Goal 4 on Education, SDG4, of the agenda. Safeguarding education against forces of privatisation and preserving it as a public good is imperative if governments are respectful of their commitments to SDG4 as well as to the 2030 Education Agenda adopted under the auspices of UNESCO. It is incumbent upon the government to expand opportunities of good quality public education to build an inclusive system of education, with positive measures in support of the poor for the eradication of widespread poverty in India. Empowering adults and youth, with a special focus on skills development and pursuit of professional excellence in the drive towards 'skilled India' to respond to rising aspirations of youth is central to the pursuit of SDG4. Actions for the implementation of SDG4 as well as 2030 Education Agenda must be guided by the principle of social justice which is enshrined in the Constitution of India.